2002
DOI: 10.1073/pnas.152259999
|View full text |Cite
|
Sign up to set email alerts
|

Energetic communication between mitochondria and nucleus directed by catalyzed phosphotransfer

Abstract: Exchange of information between the nucleus and cytosol depends on the metabolic state of the cell, yet the energy-supply pathways to the nuclear compartment are unknown. Here, the energetics of nucleocytoplasmic communication was determined by imaging import of a constitutive nuclear protein histone H1. Translocation of H1 through nuclear pores in cardiac cells relied on ATP supplied by mitochondrial oxidative phosphorylation, but not by glycolysis. Although mitochondria clustered around the nucleus, reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
122
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(128 citation statements)
references
References 44 publications
6
122
0
Order By: Relevance
“…7C, lower trace). This indicates a contribution of the AK system in the maintenance of submembrane ATP levels facilitated by AMP diffusional efflux, consistent with the demonstrated ability of AK to promote energetic communication and facilitate ATP delivery between cellular compartments [35,48].…”
Section: Nih-pa Author Manuscriptsupporting
confidence: 73%
See 3 more Smart Citations
“…7C, lower trace). This indicates a contribution of the AK system in the maintenance of submembrane ATP levels facilitated by AMP diffusional efflux, consistent with the demonstrated ability of AK to promote energetic communication and facilitate ATP delivery between cellular compartments [35,48].…”
Section: Nih-pa Author Manuscriptsupporting
confidence: 73%
“…7C, lower trace). This indicates a contribution of the AK system in the maintenance of submembrane ATP levels facilitated by AMP diffusional efflux, consistent with the demonstrated ability of AK to promote energetic communication and facilitate ATP delivery between cellular compartments [35,48].That modulation in CK flux amplifies bulk energetic signals in the vicinity of K ATP channels can be shown by the experimentally obtained relationships of ATP-induced channel inhibition measured in permeabilized cardiac cells in the presence (J CK >> 0) and absence (J CK = 0) of CrP (Fig. 7D).…”
supporting
confidence: 68%
See 2 more Smart Citations
“…For example, it was suggested that in normal smooth muscle cells the contractile functions are supported by mitochondrial ATP derived from the respiratory chain and oxidative phosphorylation (OXPHOS), whereas the plasma membrane proton pumps are supported by ATP from anaerobic glycolysis (Ishida et al, 1994). In addition, recent studies showed that the import of histones into the nuclei of neonatal cardiomyocytes is strictly dependent on a concerted interaction between mitochondrial ATP synthesis and the trafficking of high-energy phosphoryls (Dzeja et al, 2002).In a technical advance, targeted luciferase has been used as an ATP sensor to investigate the kinetics of the variation of ATP concentration beneath the plasma membrane, in the mitochondria, and in the cytosol of pancreatic ␤-cells in response to glucose stimulation (Kennedy et al, 1999). These experiments demonstrated that in response to the administration of glucose and potassium, ATP levels increased in the plasma membrane of ␤-cells in concert with that in mitochondria, whereas cytosolic ATP showed only a transient increase.…”
mentioning
confidence: 99%